Prediksi Erosi Menggunakan Metode USLE (Universal Soil Loss Equation) Pada Tanaman Kelapa Sawit (Elaeis guineensis Jacq.) - Tahir, Meisin A; Nurmi, Nurmi; Rahim, Yunnita . (Universitas Negeri Gorontalo, 2025)
Erosion is a condition that can cause damage to the surface of the land and harm humans and agricultural land, especially in oil palm plantations. The purpose of this study was to determine the predicted erosion value that occurs using the USLE method on oil palm plantations. This study was conducted in August and September 2020 at an oil palm plantation located in Sukamaju Village, Mootilango District, Gorontalo Regency. The method used in this study was a direct survey method in the field and soil sampling for analysis materials at the Soil Chemistry and Fertility Laboratory, Department of Soil Science, Faculty of Agriculture, Hasanudin University, Makassar. The results of field observations and laboratory analysis results were used to calculate the predicted erosion value on oil palm plantations using the USLE method. The results of the study showed that the amount of rain erosivity from the last 5 years (2016-2020 period) was 1615.98 joules/m2/mm, the soil erodibility value (K) was 0.29, the slope length and slope (LS) factor value was 1.09, the factor value (C) was 0.5 and the factor value (P) was 1.00 and without soil conservation measures, the predicted erosion value (A) was 255.17 tons/ha/year and was included in the heavy category.Keyword : Prediksi Erosi; USLE; Kelapa Sawit